Novel Hydrazone Chromophore Sensor for Metallochromic Determination of Cadmium Ions - Islam El-Nagar; Ahmed M. Youssef; A. A. Abd El-Hakim; El-Refaie Kenawy; Hamada S. A. Mandour; Tawfik A. Khattab (Chemosensors, 2022)
For the detection of Cd(II) in aquatic media, a novel dicyanomethylene dihydrofuran hydrazone(DCDHFH)-based colorimetric chemosensor was developed. DCDHFH was prepared by an azo-coupling process involving the diazonium chloride of 2, 4-dichloroaniline and a dicyanomethylene dihydrofuran heterocyclic moiety bearing an active methyl group. The DCDHFH chromophore showed strong solvatochromism depending on solvent polarity due to electronic delocalization. The pH sensory effects of the DCDHFH chromophore were also explored. DCDHFH could be used to identify Cd(II) in the presence of other competitive metals, as indicated by variations in color and absorbance spectra. In the presence of cadmium ions, the synthesized DCDHFH probe with hydrazone recognition moiety exhibited a significant sensitivity and selectivity to cadmium ions at the ppm concentration level (10–250 ppm). A DCDHFH-immobilized paper test strip was also prepared and effectively used for the detection of cadmium in aqueous media at various concentrations. According to CIE Lab’s criteria, colorimetric strength (K/S), and the UV–Vis absorbance spectra, the cadmium detection abilities of the DCDHFH-immobilized paper strips were evaluated. The optimal pH range for the determination of Cd(II) was monitored in the area of 5.5–6.3, with a fast chromogenic change from yellow to red relying on the Cd(II) concentration. The deposition of dicyanomethylene dihydrofuran hydrazone onto the paper strip’s surface was studied by scanning electron microscopy (SEM).